2011
DOI: 10.1002/ibd.21502
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid malabsorption in inflammatory bowel disease

Abstract: The most severe BAM occurs in CD patients after resection of the distal ileum, but BAM can occur in surgically untreated CD patients, regardless of disease localization. Laboratory tests for BAM should become a part of the algorithm for diagnosis of CD to identify patients who might respond to therapies such as bile acid sequestrants. FGF19 appears to be a reliable marker of BAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 29 publications
6
98
0
Order By: Relevance
“…Two recent studies showed slightly increased 24 or rather unchanged 25 FGF19 serum concentrations in patients with UC in comparison with healthy controls. Interestingly, however, the same studies consistently showed that patients with CD had significantly lower levels of FGF19 in serum.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Two recent studies showed slightly increased 24 or rather unchanged 25 FGF19 serum concentrations in patients with UC in comparison with healthy controls. Interestingly, however, the same studies consistently showed that patients with CD had significantly lower levels of FGF19 in serum.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, Lenicek et al 25 reported that FGF19 down-regulation only appeared in cases with a significant ileal involvement because CD patients with Crohn's colitis had normal FGF19 serum levels and only those with ileitis had significantly decreased FGF19 levels compared with controls. Consistently, in the study of Iwamoto et al, 24 the only patient with CD and a colonic inflammation had higher FGF19 levels than other CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,15,36,37 Recently, in patients with idiopathic bile acid-induced diarrhoea, FGF19 and 7a-hydroxy-4-cholesten-3-one were shown to correlate negatively and FGF19 was proposed to serve as diagnostic marker for this disease. 16 Furthermore, in diabetic patients undergoing Roux-en-Y gastric bypass, lower FGF19 levels were significantly correlated with increased hepatic expression of the CYP7A1 gene, modulating bile acid production.…”
Section: Discussionmentioning
confidence: 99%
“…IBD is associated with diarrhea, malnutrition, and weight loss through inhibited absorption of nutrients, electrolytes, and water (Sands, 2007). BAM in ileal CD was also observed in surgically untreated CD (Meihoff and Kern, 1968;Tougaard et al, 1986;Lenicek et al, 2011). However, exact molecular mechanisms for BAM in IBD are incompletely understood (Nolan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%